Measuring the impact of research outputs from the Institute for Poverty, Land and Agrarian Studies (PLAAS) on the scholarly domain and in social media, 1995-2015 - Kerchhoff, Gillian (Library and Information Studies Centre (LISC), 2017)
Scholarly communication has changed with the growth in technology, particularly the internet and the social web. The changes include a broader definition of the scholarly communication format, and the role of social media in the research process, amongst others. This study sought to record the body of work that PLAAS had produced over a 20-year period (1995 to 2015) and to measure its visibility and impact through bibliometrics and altmetrics. It was the first time that such a study had been done. The Web of Science Citation Index and Scopus are two commercial databases that have recently been joined by Google Scholar, the first open database of scholarly items with citation counts based on the entire contents of the World Wide Web. Scopus and Google Scholar were used in this study. Methods used in the study included the compilation of a full bibliographic record of the outputs during that period. Citation analysis and publication counts were conducted, per author, within Scopus and Google Scholar. Altmetric analysis was achieved with the Altmetric Explorer database, and by studying three PLAAS grey literature outputs in more depth for altmetric indicators. The last method used was a small survey based on an online multiple-choice questionnaire of researchers at PLAAS to investigate their attitudes to a selection of the social media platforms commonly used by scholars. The full list of outputs, once compiled, showed a composition of 54% grey literature published by PLAAS and 46% journal articles and monographs. The results showed that bibliometrics, as a purely quantitative indicator, can be useful in measuring the impact of a body of work on the scholarly domain and in this study indicated high publication and citation rates. The authors of the highest number of PLAAS outputs and with the highest citation counts and h-indices, were found to be the same throughout the study. These authors are closely associated with the Institute and have contributed to the good academic reputation of its research. The study was inconclusive with regard to the impact on social media platforms as none of the grey literature from PLAAS had a unique identifier which made it difficult to track; in addition, the use of social media by the Institute and its researchers was intermittent and uneven in covering all the PLAAS-published outputs that were produced. Key recommendations for PLAAS to improve the visibility and impact of their outputs in scholarly and social contexts were to use unique identifiers, to track their social media activity and to keep author profiles up to date. Further use and application of the research design in other research units and departments at UWC will generate results that are useful to research management at UWC.